Contributions of scoping review in the production of the health area: reflections and perspectives - Pétala Tuani Candido de Oliveira Salvador; Kisna Yasmin Andrade Alves; Theo Duarte da Costa; Rayssa Horacio Lopes; Lannuzya Veríssimo e Oliveira; Cláudia Cristiane Filgueira Martins Rodrigues (Universidade de Pernambuco, 2021)
Objective: to reflect on the contributions of scoping review in health production. Method: this is a reflexive study guided by the guiding question "what is the contribution of scoping review in the production of the health area?". Results: reflections are arranged in three thematic pillars: 1) conceptual and historical aspects of scoping review; 2) contributions of the scoping review in the production in the health area; and 3) advances and prospects for scoping review. Final considerations: scoping review is a type of method that meets the demands of synthesizing evidence from broad research issues, in a systematic way, with transparency and reliability of its data, which enables replication of the method by other authors. Its use in the health area follows a growing perspective and it is believed that new nuances and updates will emerge to expand the scientific robustness of this method.